Integrasi Moderasi Beragama dan Industri Halal: Tantangan dan Solusi - Saefullah, Asep; Burhanudin, Dede; Syibromalisi, Arif; Bahri, Saeful; Hardivizon, Hardivizon (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
The rapid expansion of Indonesia’s halal industry requires alignment between economic growth and the principles of religious moderation, including wasaṭiyyah (balance) and maṣlaḥah (public welfare). This study analyzes how these principles are integrated into halal governance, certification, and policy frameworks while identifying structural and socio-cultural barriers that hinder their implementation. Employing a descriptive qualitative design grounded in interpretivism, the research uses document and content analysis of legal instruments (Law No. 33/2014 on Halal Product Assurance), institutional reports (BPJPH and KNEKS), and peer-reviewed literature. Triangulation was applied through cross-validation of academic, governmental, and media sources. The findings reveal that religious moderation is conceptually acknowledged yet structurally fragmented due to bureaucratic inefficiencies, inconsistent policy coordination, and limited accessibility for micro and small enterprises (MSMEs). Cultural resistance and theological diversity further constrain its application. The study contributes to the interdisciplinary discourse on Islamic governance and ethical regulation by operationalizing wasaṭiyyah and maṣlaḥah as analytical tools for inclusive halal policymaking. It recommends strengthening regulatory coordination, digitizing halal certification, and embedding moderation training within institutional programs to enhance transparency and inclusivity. Religious moderation thus emerges not merely as a moral principle but as a structural framework for sustainable halal industry development and global competitiveness